Styrene Epoxidation over Carbon Nanotube-Supported Gold Catalysts - Liu, Junhua; Wang, Fang; Xu, Tan; Gu, Zhenggui (Catalysis letters, 2010)
Carbon nanotube supported gold catalysts prepared by deposition-precipitation with urea (DP urea) were characterized by various techniques. Its catalytic activity was examined for the oxidation of styrene using t-butylhydroperoxide as oxidant. This system showed good epoxide selectivity. The other factors, such as solvent, reaction time, concentrations of oxidant and catalyst, have also been investigated and reaction conditions are optimized. It is a novel highly active/selective and reusable heterogeneous catalyst for styrene epoxidation.